Assembly of the Intrinsic Factor X Activating Complex – Interactions between Factor IXa, Factor VIIIa and Phospholipid - van Dieijen, Gerbrand; van Rijn, Jan L M L; Govers-Riemslag, José W P; Hemker, H Coenraad; Rosing, Jan (Thrombosis and Haemostasis, 1985)
The activation of blood coagulation factor X by factor IXa is strongly stimulated by the non-enzymatic cofactors phospholipid, Ca2+ and activated factor VIII. In this paper we present a method by which we were able to determine binding affinities of factor IXa for phospholipids (either in the absence or presence of factor VIIIa) from kinetic measurements of factor X activation. It is shown that rates of factor X activation in the presence of phospholipids can be saturated with an excess factor VIIIa at limiting amounts of factor IXa and vice versa. Our data indicate that the enzymatic unit in the intrinsic factor X activator is a 1:1 stoichiometrical complex of factor IXa and factor VIIIa bound to phospholipid. Titrations with factor IXa at fixed concentrations of phospholipid and factor X show that the apparent dissociation constant of factor IXa for phospholipid is lowered from 10-6 M to 10-8 M by the presence of factor VIIIa. We conclude, that in analogy with the role of factor Va in prothrombin activation, phospholipid-bound factor VIIIa functions as a high-affinity binding site (»receptor«) for factor IXa in the intrinsic factor X activating complex. Therefore, factor VIIIa increases the observed Vmax of factor X activation by 1) enhancing the kcat of the reaction and 2) increasing the amount of phospholipid-bound factor IXa that participates in factor X activation.
Keywords: Intrinsic factor X activation; Factor VIII; Kinetics and mechanism; Binding parameters